Development of the Forensic Storage Framework using the Composite Logic method - Rachman, Helmi; Sugiantoro, Bambang; Prayudi, Yudi (ILKOM Jurnal Ilmiah, 2021)
Along with the development of information technology users, it is possible that crimes that take advantage of information technology continue to develop both directly and indirectly. Criminals often use computer devices to commit crimes. This is a major concern, so the need for handling digital evidence is very important. Therefore, a storage forensic framework is needed for handling digital evidence. This framework is designed by applying the Composite Logic method. The Composie Logic method is applied to determine the role model of each variable or initial pattern of the stages that you want to collaborate with. Composite Logic produces a role model who has a role to produce patterns so that they achieve the same goal. The logic composite method collaborates with existing frameworks for handling hdd, ssd, vmware and cloud which are then combined into a foreign storage framework. Based on the results of the tests carried out, this research has produced a new framework called the storage forensic framework. The advantage of this storage forensic framework compared to several other frameworks is that it is far required that it can be used to generate digital evidence in four storage, namely, SSD, HDD, VmWare, and cloud. This framework produces four main stages, namely preparation, collection, analysis and reports.